Hôtel de La Salle Museum photograpfic essay – Reims França - Marçal, Carolina Schwaab (2017)
This photographic essay presents a visit to the Hôtel La Salle, in Reims / France. The Hôtel La Salle was one of the places of residence of John Baptist of La Salle. It is currently a museum in honor of the Patron Saint of education and teacher training.